Genes Required for the Fitness of Salmonella enterica Serovar Typhimurium during Infection of Immunodeficient gp91(−/−) phox Mice - Grant, Andrew J. (Infect Immun, 2016)
Salmonella enterica causes systemic diseases (typhoid and paratyphoid fever), nontyphoidal septicemia (NTS), and gastroenteritis in humans and other animals worldwide. An important but underrecognized emerging infectious disease problem in sub-Saharan Africa is NTS in children and immunocompromised adults. A current goal is to identify Salmonella mutants that are not pathogenic in the absence of key components of the immune system such as might be found in immunocompromised hosts. Such attenuated strains have the potential to be used as live vaccines. We have used transposon-directed insertion site sequencing (TraDIS) to screen mutants of Salmonella enterica serovar Typhimurium for their ability to infect and grow in the tissues of wild-type and immunodeficient mice. This was to identify bacterial genes that might be deleted for the development of live attenuated vaccines that would be safer to use in situations and/or geographical areas where immunodeficiencies are prevalent. The relative fitness of each of 9,356 transposon mutants, representing mutations in 3,139 different genes, was determined in gp91(−/−) phox mice. Mutations in certain genes led to reduced fitness in both wild-type and mutant mice. To validate these results, these genes were mutated by allelic replacement, and resultant mutants were retested for fitness in the mice. A defined deletion mutant of cysE was attenuated in C57BL/6 wild-type mice and immunodeficient gp91(−/−) phox mice and was effective as a live vaccine in wild-type mice.